Zwitterionic‐polymer‐functionalized poly(vinyl alcohol‐co‐ethylene) nanofiber membrane for resistance to the adsorption of bacteria and protein. Issue 44 (26th July 2016) - Wang, Wenwen; Lu, Ying; Luo, Mengying; Zhao, Qinghua; Wang, Yuedan; Liu, Qiongzhen; Li, Mufang; Wang, Dong
ABSTRACT: A zwitterionic poly(vinyl alcohol‐ co ‐ethylene) (PVA‐ co ‐PE) nanofiber membrane for resistance to bacteria and protein adsorption was fabricated by the atom transfer radical polymerization of sulfobetaine methacrylate (SBMA). The PVA‐ co ‐PE nanofiber membrane was first surface‐activated by α‐bromoisobutyryl bromide, and then, zwitterionic SBMA was initiated to polymerize onto the surface of nanofiber membrane. The chemical structures of the functionalized PVA‐ co ‐PE nanofiber membranes were confirmed by attenuated total reflectance–Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy. The morphologies of the PVA‐ co ‐PE nanofiber membranes were characterized by scanning electron microscopy. The results show that the poly(sulfobetaine methacrylate) (PSBMA) was successfully grafted onto the PVA‐ co ‐PE nanofiber membrane, and the surface of the nanofiber membrane was more hydrophilic than that of the pristine membrane. Furthermore, the antibacterial adsorption properties and resistance to protein adsorption of the surface were investigated. This indicated that the PSBMA‐functionalized surface possessed good antibacterial adsorption activity and resistance to nonspecific protein adsorption. Therefore, this study afforded a convenient and promising method for preparing a new kind of soft and nonwoven dressing material with antibacterial adsorption and antifouling properties that has potential use in the medical field. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44169. Abstract :